Design and Synthesis of an Anticancer Diarylurea Derivative with Multiple-Kinase Inhibitory Effect - El-Gamal, Mohammed I.; Oh, Chang-Hyun (KOREAN CHEMICAL SOC, 2012)
A diarylurea compound 1 possessing pyrrolo[3,2-c]pyridine nucleus was designed and synthesized with structure similarity to Sorafenib. Compound 1 was tested over 60-cancer cell line panel at a single dose concentration of 10 mu M and showed high activity. It was further tested in a five-dose mode to determine its IC50, TGI, and LC50 values over the 60 cell lines. Compound 1 showed high potency and good efficacy, and was accordingly tested at a single dose concentration of 10 mu M over a panel of 40 kinases. At this concentration, it completely inhibited the enzymatic activities of a number of oncogenic kinases, including ABL, ALK, c-RAF, FLT3, KDR, and TrkB. The target compound was subsequently tested over these 6 kinases in 10-dose testing mode in order to determine its IC50 values.
Keywords: ANAPLASTIC LYMPHOMA KINASE; EML4-ALK FUSION GENE; CELL LUNG-CANCER; THERAPEUTIC TARGET; TYROSINE KINASE; ALZHEIMERS-DISEASE; NEUROBLASTOMA; MUTATIONS; MELANOMA; RECEPTOR